The impact of federal legislation to limit electronic monitoring. - Greenlaw PS; Prundeanu C (Public Personnel Management)
Organizations are increasingly using technology to electronically monitor employees' telephone calls, computer use and even their physical location. Electronic monitoring's popularity is largely driven by organizational security problems and the need to measure employee performance. However, there is growing concern, particularly among employee groups and some legislators, that guidelines are needed to ensure these technologies are used responsibly and do not infringe on employee rights. Additionally, the effectiveness of unlimited electronic monitoring as a management tool is being questioned. The Privacy for Consumers and Workers Act (PCWA) was drafted in response to these concerns, and has been vigorously debated in both the House and the Senate. This article will address key arguments raised both in support of and in opposition to this legislation. Although the PCWA did not become law, the complex issues raised by unrestricted electronic monitoring of employees are likely to remain on the public policy agenda.